2015
DOI: 10.19030/jabr.v31i5.9385
|View full text |Cite
|
Sign up to set email alerts
|

Does Crime Influence The Payment Decisions Of Consumers?

Abstract: The impact of crime on economic activity has been widely studied. The economic analysis of crime on payment instrument, however, is still lacking. In this paper, we analyze the impact of crime on the use of cash and card payment with an original database of a representative sample of French consumers. We provide empirical evidence that violent and financial crimes have opposite effects on cash withdrawn and cash payment: On the one side, violent crime increases the amount of cash withdrawn and increases the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…It supports a positive money-crime relationship when money is subject to theft. For instance, referring to the theoretical foundations of the Baumol-Tobin model 6 , (Karoubi and Chenavaz, 2015) showed that the higher the incidence of violent crime, i.e., violent theft and street crime, the higher the weekly amount of cash withdrawn, and, they also found a negative correlation between violent theft and the decision of having a paying card. These results may seem counterintuitive, as reduced money holdings seems like the way to diminish the size of expected losses in the event of property crime.…”
Section: Literature Review On Crime and Moneymentioning
confidence: 99%
“…It supports a positive money-crime relationship when money is subject to theft. For instance, referring to the theoretical foundations of the Baumol-Tobin model 6 , (Karoubi and Chenavaz, 2015) showed that the higher the incidence of violent crime, i.e., violent theft and street crime, the higher the weekly amount of cash withdrawn, and, they also found a negative correlation between violent theft and the decision of having a paying card. These results may seem counterintuitive, as reduced money holdings seems like the way to diminish the size of expected losses in the event of property crime.…”
Section: Literature Review On Crime and Moneymentioning
confidence: 99%